Nlrp12 deficiency alters gut microbiota and ameliorates Faslpr-mediated systemic autoimmunity in male mice - Abdelhamid, Leila; Mao, Jiangdi; Cabana-Puig, Xavier; Zhu, Jing; Swartwout, Brianna K.; Edwards, Michael R.; Testerman, James C.; Michaelis, Jacquelyn S.; Allen, Irving Coy; Ahmed, S. Ansar; Luo, Xin M. (Frontiers in Immunology, 2023)
NLRP12 has dual roles in shaping inflammation. We hypothesized that NLRP12 would modulate myeloid cells and T cell function to control systemic autoimmunity. Contrary to our hypothesis, the deficiency of Nlrp12 in autoimmune-prone B6.Faslpr/lpr mice ameliorated autoimmunity in males but not females. Nlrp12 deficiency dampened B cell terminal differentiation, germinal center reaction, and survival of autoreactive B cells leading to decreased production of autoantibodies and reduced renal deposition of IgG and complement C3. In parallel, Nlrp12 deficiency reduced the expansion of potentially pathogenic T cells, including double-negative T cells and T follicular helper cells. Furthermore, reduced pro-inflammatory innate immunity was observed, where the gene deletion decreased in-vivo expansion of splenic macrophages and mitigated ex-vivo responses of bone marrow-derived macrophages and dendritic cells to LPS stimulation. Interestingly, Nlrp12 deficiency altered the diversity and composition of fecal microbiota in both male and female B6/lpr mice. Notably, however, Nlrp12 deficiency significantly modulated small intestinal microbiota only in male mice, suggesting that the sex differences in disease phenotype might be gut microbiota-dependent. Together, these results suggest a potential pathogenic role of NLRP12 in promoting systemic autoimmunity in males. Future studies will investigate sex-based mechanisms through which NLRP12 differentially modulates autoimmune outcomes.